Geospatial Analysis of Rainfall Variability Impacts on Crop Yield in the Guinea Savanna Ecological Zone of Nigeria - Ayanlade, Ayansina (2015)
The study developed a GIS database on inter-annual rainfall variability and crop yield in the Guinea Savanna ecological zone of Nigeria; mapped inter-annual changes in crop yield as a response to inter-annual rainfall variability in the study area. It also related the spatio-temporal variability in rainfall with crop yields; and model future scenario of the impact of rainfall variability on crop yields. This was with a view to evaluating the spatio-temporal impacts of rainfall variability on crop yields in the area.